2004
DOI: 10.1101/gad.1235904
|View full text |Cite
|
Sign up to set email alerts
|

Elongation by RNA polymerase II: the short and long of it

Abstract: Appreciable advances into the process of transcript elongation by RNA polymerase II (RNAP II) have identified this stage as a dynamic and highly regulated step of the transcription cycle. Here, we discuss the many factors that regulate the elongation stage of transcription. Our discussion includes the classical elongation factors that modulate the activity of RNAP II, and the more recently identified factors that facilitate elongation on chromatin templates. Additionally, we discuss the factors that associate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
588
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 614 publications
(609 citation statements)
references
References 369 publications
19
588
1
1
Order By: Relevance
“…[2][3][4] We therefore generated mice lacking one of these factors, Elongin A. Elongin A À/À embryos were severely retarded in development and died between days 10.5 and 12.5 of gestation, most likely owing to extensive apoptosis. Moreover, MEFs derived from Elongin A À/À embryos exhibited not only increased apoptosis but also senescence-like growth defects, accompanied by the activation of p38 MAPK and p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] We therefore generated mice lacking one of these factors, Elongin A. Elongin A À/À embryos were severely retarded in development and died between days 10.5 and 12.5 of gestation, most likely owing to extensive apoptosis. Moreover, MEFs derived from Elongin A À/À embryos exhibited not only increased apoptosis but also senescence-like growth defects, accompanied by the activation of p38 MAPK and p53.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition, a diverse collection of elongation factors that promote efficient elongation of transcripts by pol II in vitro have also been identified. [2][3][4] These factors fall into two broad functional classes based on their ability to either reactivate arrested pol II or suppress the transient pausing of pol II. The first class is composed of members of the SII family.…”
mentioning
confidence: 99%
“…It has been suggested that promoters with preloaded RNAP can respond to activation signals more "quickly" and uniformly (Boettiger and Levine, 2009). In addition, paused RNAP has been suggested to provide a checkpoint to ensure a successful coupling between transcription and mRNA processing or to prevent "mistakes" during the transcription process (Sims et al, 2004a;Levine, 2011).…”
Section: Promoter Clearance and Release Of Paused Rnapmentioning
confidence: 99%
“…Many proteins (or complexes) have been identified that play important roles in facilitating transcription elongation, and some of these factors represent targets for activators (Sims et al, 2004a;Peterlin and Price, 2006). For example, experiments in Drosophila suggested that the elongation factor P-TEFb is recruited to the heat shock loci to facilitate transcription elongation upon heat shock induction (Lis et al, 2000).…”
Section: Promoter Clearance and Release Of Paused Rnapmentioning
confidence: 99%
“…Whereas pre-initiation and initiation steps of transcription involve multiple levels of regulation, there are now accumulating evidences for transcriptional elongation being a tightly regulated process that requires a plethora of proteins, for example the elongation factors [21] such as TFIIF, TFIIH, and the multi-protein complex FACT [22]. In this context, gene transcription in response to DNA-damaging agents relies on gene-and signal-specific elongation factors [23].…”
Section: Introductionmentioning
confidence: 99%